Intestinal Organoids as a Tool for Inflammatory Bowel Disease Research - Angus, Hamish C. K.; Butt, A. Grant; Schultz, Michael; Kemp, Roslyn A. (Frontiers in Medicine, 2020)
Inflammatory bowel diseases (IBD) are difficult to model as freshly acquired tissues are short-lived, provide data as a snapshot-in-time, and are not always accessible. Many patients with IBD are non-responders to first-line treatments, and responders are prone to developing resistance to treatment over time – resulting in reduced patient quality of life, increased time to remission, and potential relapse. IBDs are heterogenous and we are yet to fully understand the mechanisms of disease; thus, our ability to diagnose and prescribe optimal treatment remains ineffective. Intestinal organoids are derived from patient tissues expanded in vitro. Organoids offer unique insight into individual patient disease and are a potential route to personalized treatments. However, organoid models do not contain functional microbial and immune cell components. In this review, we discuss immune cell subsets in the context of IBD, and the requirement of immune cell and microbial components in organoid models for IBD research.